A conversation analytic approach to schizophrenic interaction: methodological reflections on disruptions of the common-sense world - Smith, R. G.; Stirling, Lesley (Frontiers in Sociology, 2023)
Certain schools of phenomenological psychiatry conceive of schizophrenia as a pathology of common-sense. Ethnomethodological enquiry, with its roots in Schutzian social phenomenology, takes as its domain, topic and substance of study the ongoing achievement of a common-sense world between social members. Yet dialogue between psychiatry and ethnomethodological approaches is thin.In this article we discuss a conversation analytic approach to schizophrenic interaction which has generated and utilised a model of a five-world manifold to frame analyses of talk-in-interaction. 'Worlds' are conceived, after Schutz, as finite domains of meaning, and the model operates as a breach of natural attitude assumptions in order to examine mechanisms of constitution of the oneworld-in-common of common-sense. It is suggested that certain aspects of schizophrenic talk might receive account in terms of a loss of integration between these five domains of meaning.Conversation Analytic methods were applied to transcripts of audio recordings of psychiatric interviews, but encountered hurdles that motivated a broadening of methodological scope. Such hurdles included a weakening of next turn proof procedure, implicit reification of the schizophrenia construct, and problems of translation presented by the analyst's normative membership encountering non-normative life-worlds of schizophrenic experience. Strategic responses to these hurdles included exploring linkages between phenomenological psychiatry and ethnomethodological approaches as well as an engagement of ethnomethodological self-reflection and conceptual clarification of the schizophrenia construct in line with Garfinkel's unique adequacy requirement. The manifold model is glossed and interaction between two of these worlds-a world of concrete, situational immediacies and another of abstract organisations-is explored in more detail via analysis of conversational data.It is suggested that the five-world model along with further micro-analysis of talk-in-interaction might have implications in psychiatry for topics such as: autism; double bookkeeping; concretism; theories of disturbed indexicality, and insight attribution. We conclude that consideration of atypical interaction obliges the interaction analyst to take account of their own implicit normative world-frames and that the use of domain specific top-down models in conjunction with the inductive approach of Conversation Analysis may extend the reach of CA to facilitate productive dialogue with other disciplines.